Perioperative Predictors of Free Flap Damage in Head and Neck Surgery: A Retrospective Cohort Study - Máximo, Maria Ana; Serafino, Sara; Carvalho, Susana (Journal of the Portuguese Society of Anesthesiology, 2019)
Introduction: Microvascular free flap surgery improves survival and life quality. However, we lack knowledge on the best anesthesia approach. We aimed to identify predictors of flap damage. Material and Methods: Eighty-seven patients submitted to head and neck free flap surgery were analyzed. The primary endpoint was flap damage (composite of complete flap loss, wound infection and 30-day re-intervention). Results: Flap damage occurred in 18.6% patients (n=16). Body mass index was significantly different between groups. Patients with flap damage had a median body mass index of 20.56 [IQR 4.01] compared to 22.03 [IQR 5.02] in the control group. Body mass index had a significant discriminatory power for predicting flap damage (AUC 0.67 CI: 0.54-0.81). With a cut-off body mass index of 21, lower body mass index patients were at increased risk for flap damage (OR 3.96; CI: 1.24-12.69). They were more frequently mechanically ventilated >48 hours (56.3% vs 17.4%, p<0.05) or received postoperative blood transfusion (56.3% vs 20,3%, p <0.05). They had longer ICU (6.5 IQR 6 vs 4 IQR 4, p <0.05) and in-hospital stays (37.5 IQR 36 vs 18 IQR 17, p<0.05). Discussion: Nutritional status should be a priority during patient selection. The association to mechanical ventilation, postoperative blood transfusion and prolonged in-intensive care unit stays reinforces the need for optimal postoperative care. Conclusion: Body mass index, mechanical ventilation, postoperative blood transfusion, longer intensive care unit and in-hospital stays were predictors of flap damage. Anesthesiologists should assume a coordinated perioperative medicine. Further studies are needed to clarify relevant practices.